2021
DOI: 10.1002/aepp.13162
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions after long‐term use of alternative irrigation water: A field experiment in Israel

Abstract: This study provides the first revealed preference estimates of Israelis' willingness to pay for produce irrigated with alternative water. Results show that Israelis prefer produce irrigated with conventional water over any type of alternative water and that their preferences for alternative water varies by type. These results indicate that there may be long‐run limits to how high consumer demand for alternative water can rise. Policymakers should be cognizant of these findings and gradually expose the public t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 50 publications
(68 reference statements)
1
13
0
Order By: Relevance
“…Savchenko et al (2018) determined that consumers had lower WTP for produce irrigated with recycled water versus conventional water or an unknown irrigation water source. Similarly, Ellis et al (2021) found that among Israeli consumers demand for agricultural produce declined significantly when irrigated with recycled water versus conventional or an unspecified source of water. This result is particularly interesting given Israel's over 36-year history of alternative water use.…”
Section: Environmental Conservationmentioning
confidence: 98%
See 2 more Smart Citations
“…Savchenko et al (2018) determined that consumers had lower WTP for produce irrigated with recycled water versus conventional water or an unknown irrigation water source. Similarly, Ellis et al (2021) found that among Israeli consumers demand for agricultural produce declined significantly when irrigated with recycled water versus conventional or an unspecified source of water. This result is particularly interesting given Israel's over 36-year history of alternative water use.…”
Section: Environmental Conservationmentioning
confidence: 98%
“…There is thus a question regarding the extent to which processes such as negative information campaigns, such as occurred in Toowoomba (Citizens Against Drinking Sewage), may amplify risk perceptions and affect public responses to the identified effective messaging practices, as explained by Kemp et al (2012). Ellis et al (2021) found that exposing consumers to information about the risks and benefits (two-sided messages) of recycled wastewater increased consumers' WTP for produce irrigated with desalinated water. The aversion to recycled irrigation water is likely due to disgust because of its source and/or concerns about potential health risks (Ellis et al 2021).…”
Section: Disgust As More Than Simple Revulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…Israel's experience in water management (Menahem 2001;IWA 2009;Opher & Friedler 2016;Ellis et al 2021) can lead the way forward for countries interested in alleviating drinking water scarcity. The Israeli population has dealt with water shortages for decades.…”
Section: Perceptions Among Israelismentioning
confidence: 99%
“…To avoid the need for total reliance on desalination, household demand should be reduced using all available technologies and practices. Ellis et al (2021) attribute Israelis high willingness to pay (WTP) for food grown using alternative water sources (defined as any water source other than conventional ones, such as groundwater and treated surface water, is considered alternative, including desalinated seawater and recycled household wastewater) to the fact that Israel, has been using alternative irrigation water on a nationwide scale for over three decades. Yet, Ellis et al (2021) also point out that surprisingly few studies have investigated Israeli consumers' perceptions of this reuse strategy.…”
Section: Perceptions Among Israelismentioning
confidence: 99%